Cadrages médiatiques et logiques commémoratives du discours à propos de sciences - Joëlle Le Marec; Igor Babou (Communication)
How do two media as different as an exhibition and television treat the same scientific theme of radioactivity? Do the effects of frames (ideological, institutional, structural) organize the different representations of the theme? To answer these questions, we have mobilized a comparative analysis which profits from the conjuncture of two commemorations which are linked to the theme of radioactivity: the tenth anniversary of the Chernobyl disaster and the 100th anniversary of the discovery of radioactivity. Everything appears as if, in both cases, the medium «uses» the commemoration to make its privileged mode of legitimization work, to put it to the test, and to make it visible for all as a set of directives. This analysis shows the extent to which the media treatment of the same theme depends on conceptions of the relationship between science, media, and society which are not self-evident and which are described with precision and on empirical bases herein.